2015
DOI: 10.5812/aapm.23409
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inhalational Anesthetic Drugs in Patients with Hepatic Dysfunction: A Review Article

Abstract: Context:Anesthetic drugs including halogenated anesthetics have been common for many years. Consequent hepatic injury has been reported in the literature. The mechanism of injury is immunoallergic. The first generation drug was halothane; it had the most toxicity when compared to other drugs. The issue becomes more important when the patient has an underlying hepatic dysfunction.Evidence Acquisition:In this paper, reputable internet databases from 1957–2014 were analyzed and 43 original articles, 3 case report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
(49 reference statements)
0
11
0
3
Order By: Relevance
“…Liver disease is the tenth most common cause of death in the United States leading to 25000 deaths every year ( 5 , 6 ). Liver disorders are classified into two groups: acute and chronic.…”
Section: Contextmentioning
confidence: 99%
“…Liver disease is the tenth most common cause of death in the United States leading to 25000 deaths every year ( 5 , 6 ). Liver disorders are classified into two groups: acute and chronic.…”
Section: Contextmentioning
confidence: 99%
“…32,33 Agents producing hepatitis are generally toxins and poisons that are converted to toxic metabolites. 33,34,36 Clinical manifestations are highly variable, ranging from asymptomatic with elevated liver enzymes to fulminant hepatic failure. Acetaminophen can cause fulminant hepatic failure after an overdose and can also induce chronic hepatic injury in analgesic doses to those who have chronic alcoholism and existing impaired liver function/liver damage.…”
mentioning
confidence: 99%
“…Acetaminophen can cause fulminant hepatic failure after an overdose and can also induce chronic hepatic injury in analgesic doses to those who have chronic alcoholism and existing impaired liver function/liver damage. 33,34 Ethanol has been show to induce the CYP 2E1 isoenzyme, which is primarily responsible for production of the toxic metabolite of acetaminophen, N-acetyl-p-benzoquinone imine. Studies have shown up to a 22% increase in the toxic metabolite after administration of 500 mg acetaminophen in healthy adults.…”
mentioning
confidence: 99%
“…The flurane family of drugs reduces mean arterial pressure and cardiac output and, consequentially, reduces hepatic blood flow. Halothane, no longer available in the United States, has been associated with hepatotoxicity and should not be used in patients with cirrhosis …”
Section: Medications Used In Sedation For Endoscopymentioning
confidence: 99%